Analytical Study Of The Impact Of The Corona Pandemic On The Tourism Demand For Accommodation Facilities In Lattakia Governorate (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The study focused on the following problem: Is there an impact of the Corona pandemic on the tourist demand for accommodation facilities in Lattakia Governorate?. The study aimed at the following: To clarify the reality of the tourist demand for accommodation facilities before the Corona pandemic, in addition to determining the changes in the structure of the tourist demand in the accommodation facilities (hotels, chalets and furnished apartments, and visitors) during the period of the Corona pandemic in the Lattakia Governorate in 2020. A descriptive analytical approach was used.The study found a set of results, the most important of which are: The Corona pandemic affected the overall tourism demand for accommodation facilities in the Lattakia Governorate significantly in 2020 compared to 2019, There is an improvement in the overall tourism demand for accommodation facilities in the Lattakia Governorate in the three years before the pandemic. The pandemic affected the components of the Tourism Demand (hotels, furnished apartments, visitors) in Lattakia Governorate in 2020, The tourist demand for hotels was affected less than the Tourism demand for chalets, apartments, and visitors.